2006
DOI: 10.4304/jmm.1.2.14-20
|View full text |Cite
|
Sign up to set email alerts
|

Fast Image Mosaicing for Panoramic Face Recognition

Abstract: Abstract-In this article, we present some development results of a system that performs mosaicing (or mosaicking) of panoramic faces. Our objective is to study the feasibility of panoramic face construction in real-time. To do so, we built a simple acquisition system composed of 5 standard cameras which, together, can take simultaneously 5 views of a face at different angles. Then, we chose an easily hardware-achievable algorithm, consisting of successive linear transformations, in order to compose a panoramic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…As a next step, we would like to integrate our multi-view face acquisition framework with multi-view face recognition techniques and quantify the achievable recognition performance [2], [3], [4], [5]. In particular, we would like to integrate our system with sparse encoding based recognition techniques [27] that are especially well-suited for distributed light-weight implementations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a next step, we would like to integrate our multi-view face acquisition framework with multi-view face recognition techniques and quantify the achievable recognition performance [2], [3], [4], [5]. In particular, we would like to integrate our system with sparse encoding based recognition techniques [27] that are especially well-suited for distributed light-weight implementations.…”
Section: Discussionmentioning
confidence: 99%
“…Often profile (side view) face images contain tattoos, moles and special markers that are useful in human identification [1]. Recent studies have shown that profile views and partial profile views can be used for reliable face recognition with high accuracy [2], [3], [4], [5]. That being said, acquiring multi-view face images is a challenging task in terms of computational overhead especially due to their diversity [6].…”
Section: Introductionmentioning
confidence: 99%
“…The POI matching process is as follows: the markers are respectively detected in both images by using a color threshold method [30]. It performs a color segmentation based on the hue and the saturation components of each image.…”
Section: Detection and Matching Of Poismentioning
confidence: 99%
“…It is used in various domains such as medicine [32], security [30], virtual reality or robotics Multimed Tools Appl (2012) 57:565-586 …”
Section: Introductionmentioning
confidence: 99%
“…Images of different quality (pose, illumination and resolution) continually stream in from multiple cameras which need to be efficiently utilized. [2,3,4,5]. That being said, acquiring multi-view face images is a challenging task in terms of computational overhead especially due to their diversity [6].…”
Section: Notationmentioning
confidence: 99%